Capnocytophaga canimorsus meningitis and bacteraemia without a dog bite in an immunocompetent individual. Issue 7 (21st July 2021) - O'Riordan, Fiona; Ronayne, Aoife; Jackson, Arthur
Abstract : We describe the case of an immunocompetent 75-year-old man with Capnocytophaga canimorsus bacteraemia and meningitis. C. canimorsus is commonly found in the oral flora of dogs with human infection typically occurring following a bite. Unusually, while our patient was a dog owner, there was no history of bite nor scratch mark. Admission blood cultures flagged positive for Gram-negative bacilli, but prolonged molecular analysis was required before C. canimorsus was isolated in blood and cerebrospinal fluid. There is a high mortality rate in invasive infection, and in our patient's case, antibiotic therapy was commenced prior to laboratory confirmation with our patient making a complete recovery. This case highlights the importance of including C. canimorsus in the differential diagnosis of unwell patients who keep dogs, even without a bite. This case occurred amid heightened awareness of COVID-19, which may represent predisposition for zoonoses during social isolation and increased human–pet contact.